2008
DOI: 10.1007/s00464-008-9898-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized blinded trial comparing the cardiopulmonary effects of NOTES with standard laparoscopy in a porcine survival model

Abstract: Significant differences in measured but not clinically apparent cardiopulmonary parameters were encountered. The difference in insufflation gas, different vagal or catecholamine response may be contributing to these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…The invasive monitoring showed a widening pulse pressure in the NOTES group compared with the laparoscopy group after 60 min of the procedure (p \ 0.001) and a significantly lower mean bladder pressure in the NOTES group (p \ 0.001). These results are described in detail elsewhere [9].…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The invasive monitoring showed a widening pulse pressure in the NOTES group compared with the laparoscopy group after 60 min of the procedure (p \ 0.001) and a significantly lower mean bladder pressure in the NOTES group (p \ 0.001). These results are described in detail elsewhere [9].…”
Section: Resultssupporting
confidence: 56%
“…Gastric irrigation in the NOTES animals caused a significant drop in bacterial contamination (p \ 0.001) [9]. Postoperatively, one animal in the NOTES group experienced erosive gastritis and succumbed to an upper gastrointestinal bleed on postoperative day 3.…”
Section: Resultsmentioning
confidence: 99%
“…The need for research in the field of physiology, infection of the access point, and development of new devices, among other issues [22] have also been discussed. Recent experimental studies are providing an understanding of the physiologic effects of insufflation and infection in natural orifice surgery [23][24][25][26][27][28][29]. Insufflation with ambient air promoted through the working or insufflation channel of the endoscope proved to be dangerous and unreliable in experimental settings [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Data from a previous randomized blinded study with the porcine model showed a significant difference in heart rate and diastolic blood pressure (DBP) between NOTES and standard laparoscopy animals [15]. The laparoscopic animals became significantly more tachycardic and experienced a rise in DBP compared with the NOTES animals,…”
mentioning
confidence: 97%
“…To our knowledge, no data evaluating the hemodynamic impact of the new approach in the human environment are currently available. The hemodynamic reaction, however, could be considered an important proxy for the invasiveness of the new approach.Data from a previous randomized blinded study with the porcine model showed a significant difference in heart rate and diastolic blood pressure (DBP) between NOTES and standard laparoscopy animals [15]. The laparoscopic animals became significantly more tachycardic and experienced a rise in DBP compared with the NOTES animals,…”
mentioning
confidence: 99%